Filaggrin failure – from ichthyosis vulgaris to atopic eczema and beyond. (1st October 2016) - McLean, W.H.I.
Summary: The main proteinaceous component of the keratohyalin granules within the granular layer keratinocytes of the epidermis is the giant, repetitive polyprotein profilaggrin. When granular layer cells commit to terminal differentiation to form the flattened squames of the stratum corneum, profilaggrin is rapidly cleaved into multiple copies of the 37 kDa filaggrin monomer, which binds to and condenses the keratin cytoskeleton, thereby facilitating cellular compression. Within the stratum corneum, filaggrin is broken down to form natural moisturising factor, a pool of amino acids and derivatives thereof that exerts multiple effects. Filaggrin is therefore essential for normal stratum corneum biogenesis and physiology. In 2006, the McLean group identified the first loss‐of‐function mutations in the filaggrin gene ( FLG ) as the cause of the common monogenic genodermatosis ichthyosis vulgaris (IV). In parallel, they showed by multiple methods that these mutations, carried by up to 10% of various human populations are the major genetic predisposing factor for atopic dermatitis (eczema) and all of the associated allergic phenotypes that constitute the atopic diathesis. This paradigm‐shifting work showed that skin barrier deficiency is a major early event in the pathophysiology of eczema and allergy.